The Lis1-Related Nudf Protein of Aspergillus nidulans Interacts with the Coiled-Coil Domain of the Nude/Ro11 Protein - Efimov, Vladimir P. (The Rockefeller University Press, 2000)
The nudF gene of the filamentous fungus Aspergillus nidulans acts in the cytoplasmic dynein/dynactin pathway and is required for distribution of nuclei. NUDF protein, the product of the nudF gene, displays 42% sequence identity with the human protein LIS1 required for neuronal migration. Haploinsufficiency of the LIS1 gene causes a malformation of the human brain known as lissencephaly. We screened for multicopy suppressors of a mutation in the nudF gene. The product of the nudE gene isolated in the screen, NUDE, is a homologue of the nuclear distribution protein RO11 of Neurospora crassa. The highly conserved NH(2)-terminal coiled-coil domain of the NUDE protein suffices for protein function when overexpressed. A similar coiled-coil domain is present in several putative human proteins and in the mitotic phosphoprotein 43 (MP43) of X. laevis. NUDF protein interacts with the Aspergillus NUDE coiled-coil in a yeast two-hybrid system, while human LIS1 interacts with the human homologue of the NUDE/RO11 coiled-coil and also the Xenopus MP43 coiled-coil. In addition, NUDF coprecipitates with an epitope-tagged NUDE. The fact that NUDF and LIS1 interact with the same protein domain strengthens the notion that these two proteins are functionally related.